The performance of tungsten carbide end-mills in micro-milling of Ti-6Al-4V under nitrogen cooling - Engelbrecht, Maria Elizabeth (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.